Understanding The Impact of Mentorship, Marketing Skills, And Personality Traits on Career Readiness Of Gen Z Apprentices - Siska Purnama Manurung; Elsadai Dwi Prastiani (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study explores the effects of mentorship, marketing skills, and personality traits on the career readiness of Generation Z interns in Indonesia. As organizations face rapid market evolutions, understanding how these factors influence early career success becomes essential. This research addresses the gap in quantitative evidence linking these variables with career outcomes in the Indonesian context. A quantitative survey was conducted among 19–34-year-old Gen Z interns across various industries, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that mentorship, marketing skills, and personality traits significantly predict career readiness both individually and collectively. These findings suggest that educational institutions and business organizations should enhance their training programs to better prepare young professionals for the competitive job market, emphasizing the development of essential marketing skills and positive personality traits alongside robust mentorship. This study contributes to the literature by highlighting specific employability factors critical for Generation Z, offering insights into stakeholders involved in career development and talent management.